Reactivity difference in the oxidative nucleophilic reaction of peroxonickel(iii) intermediates with open-chain and macrocyclic systems. Issue 8 (15th July 2019) - Yun, Seonggeun; Kwon, Nam; Kim, Seonghan; Jeong, Donghyun; Ohta, Takehiro; Cho, Jaeheung
Abstract : The open-chain peroxonickel(iii ) intermediate is much more reactive than the macrocyclic analogue in aldehyde deformylation. Abstract : A peroxonickel(iii ) complex bearing the Me6 -trien ligand, an open-chain analogue of the macrocyclic 12-TMC ligand, was synthesized and characterized by several physical methods, such as UV-vis, resonance Raman, ESI-MS and EPR. Density functional theory calculations provide geometric and electronic configurations of peroxonickel(iii ) complexes. The reactivity of the peroxonickel(iii ) intermediate was examined in oxidative nucleophilic reactions ( e.g., aldehyde deformylation). By comparing the reactivities of the open-chain and macrocyclic peroxonickel(iii ) complexes under identical reaction conditions, we were able to demonstrate that the open-chain peroxonickel(iii ) complex is much more reactive than the macrocyclic analogue in aldehyde deformylation. This result provides intriguing aspects of the reactivity differences for open-chain vs . macrocyclic systems of metal complexes.